2008
DOI: 10.1088/0953-2048/21/12/125017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of the BaSnO3insertion effect on the properties of YBa2Cu3O7−xfilms prepared by pulsed laser ablation

Abstract: YBa 2 Cu 3 O 7−x + BaSnO 3 (YBCO + BSO) mixed films with increasing BSO content were prepared on SrTiO 3 substrates by pulsed laser deposition from YBCO + x wt% BSO mixed targets (x = 2, 3, 4, 5, 6, 8 and 9 wt%). Transmission electron microscopy (TEM) images reveal that BSO is incorporated into the YBCO matrix in form of nanorods, whose density and size increase with increasing BSO content. The pinning properties for the mixed YBCO + BSO film were systematically studied. The 4 wt% sample presents the maximum g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 46 publications
8
46
0
Order By: Relevance
“…The reason for the increases of c-axis length may possibly be Zr substitution for copper atoms in the YBCO structure. The same effect was previously reported for YBCO-BaSnO 3 [9] and ErBCO-BaNb 2 O 6 [10] systems. The behaviour can be explained by ionic radii for coordination number 6, typical for B-position of perovskite structure: Ce …”
Section: Cation Composition Of Films With Bzo and Bco Inclusionssupporting
confidence: 88%
“…The reason for the increases of c-axis length may possibly be Zr substitution for copper atoms in the YBCO structure. The same effect was previously reported for YBCO-BaSnO 3 [9] and ErBCO-BaNb 2 O 6 [10] systems. The behaviour can be explained by ionic radii for coordination number 6, typical for B-position of perovskite structure: Ce …”
Section: Cation Composition Of Films With Bzo and Bco Inclusionssupporting
confidence: 88%
“…Recently there have been many reports indicating that incorporating second-phase nanosized particles such as BaZrO 3 , BaSnO 3 , NbO 2 or defects enhances the pinning force for YBa 2 Cu 3 O 7−δ [10][11][12]. Jongprateep et al had reported that the addition of BaCeO 3 to YBCO results in an enhancement in the critical current density.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] High critical current densities are being pursued in REBCO superconducting tapes in high magnetic fields (2-30 T) in a temperature range of 4.2 K-50 K for use of these materials in electric power applications such as motors, generators, superconducting magnetic energy storage (SMES) as well as in high energy particle accelerators, magnetic resonance imaging, and high-field magnets. Introduction of Y 2 BaCuO 5 , 8 BaZrO 3 (BZO), [9][10][11][12][13] BaSnO 3 ,14,15 BaHfO 3 , 16 Ba 2 YNbO 6 , 17,18 and Gd 3 TaO 7 19 nanoscale defects in the REBCO films of the superconducting tapes has been proven to be a powerful method to increase critical current density (J c ) of these tapes via enhanced flux pinning by these defects. Until recently, high J c in REBCO films with BaMO 3 (M ¼ Zr, Sn, and Hf) nanoscale defects has been obtained only with less than 10 mol.…”
mentioning
confidence: 99%
“…Until recently, high J c in REBCO films with BaMO 3 (M ¼ Zr, Sn, and Hf) nanoscale defects has been obtained only with less than 10 mol. % of dopants in films made by pulsed laser deposition (PLD), [9][10][11][14][15][16] metal organic deposition, 12 and metal organic chemical vapor deposition (MOCVD). 13 Such moderately doped REBCO films have been optimized for high J c in low magnetic fields at 77 K and, as such, do not exhibit exemplary performance in conditions of interest for practical applications, i.e., temperatures less than 50 K and fields of 2-30 T. A sharp reduction in the superconducting transition temperature (T c ) in films with high levels of BaMO 3 addition resulted in low J c 15 and hence, heavily doped REBCO films have been generally avoided by most researchers.…”
mentioning
confidence: 99%